Modern Methods of Quality Management - Anastasia Kurilova; Dmitry Savenkov (Communications of International Proceedings, 2020)
The relevance of improving quality management methods at enterprises is explained by the fact that in recent years, modern progressive enterprises are aimed at improving the quality of products and services by introducing quality tools and methods into the organization. Quality management is a lever for the economic development of the organization, the improvement of quality management methods directly affects the increase in the productivity of the enterprise, leads to the optimization of production costs. Improving quality management methods increases one of the most important criteria for assessing an organization - its competitiveness.
Keywords: Quality; Quality Management; Competitiveness; Costs; Costs; Statistical Process Control; Systems Approach; Quality Management.